Evaluating the Effectiveness of the Learning Community Program in Improving Educators’ Pedagogical Competence - Trisna Apriani; Manap Somantri; Muhammad Kristiawan; Zaharah Hussin (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to evaluate the learning community program at Sekolah Pendidikan Non-Formal Sanggar Kegiatan Belajar [Non-Formal Education School Learning Activity Center] SPNF-SKB Kaur in improving the pedagogical competence of learning facilitators using the CIPP (Context, Input, Process, Product) evaluation model. Methodology: This research employed a descriptive qualitative approach with the CIPP model. Participants included the Head of SPNF-SKB Kaur, learning community managers, and learning facilitators. Data were collected through interviews, observations, and documentation, then analyzed using Miles, Huberman, and Saldaña’s interactive model, including reduction, display, verification, and conclusion drawing. Main Findings: The findings show that the learning community program is relevant and effectively managed. It successfully supports planning, implementation, and resource provision, leading to improved pedagogical competence of facilitators and positive impacts on student learning outcomes. Nevertheless, challenges remain, such as limited motivation among some facilitators, insufficient module availability for Package A and B, and suboptimal support from local government. Novelty/Originality of this study: This study provides one of the first comprehensive evaluations of a learning community program for facilitators in non-formal education. Unlike previous studies that focused mainly on teachers in formal schools, this research highlights both the effectiveness and challenges of learning communities in enhancing pedagogical competence in non-formal education settings, filling an important gap in the literature.